AKAR BANALITAS INTELEKTUAL (SUATU KAJIAN FILSAFAT ILMU) - Anastasia Jessica Adinda S. (Jurnal Filsafat "WISDOM", 2013)
This research starts from the problems of education in Indonesia in which Heru Nugroho call them “intellectual banality”. The intellectual banality is a situation which is characterized by unconscious superficiality of thought, and degradation of intellectual and academic quality. Basic idea of this research is to look for roots of the intellectual banality at the level of philosophy of science because educational practices presuppose a perspective to science. Roots of the intellectual banality in this research are: first, there is a priority of quantitative perspective to measure intellectual quality. Prioritization of the quantitative perspective can be viewed as a romanticism of induction method triumph;.second, ignorance the aim of science which is create the humanitarian welfare in general, not only one or a small group of person.